The scarlet letter - Hawthorne, Nathaniel, 1804-1864.; Moser, Barry (San Diego : Harcourt Brace Jovanovich, 1986)
In early colonial Massachusetts, a young woman endures the consequences of her sin of adultery and spends the rest of her life in atonement.
Keywords: Triangles (Interpersonal relations) -- Fiction; Illegitimate children -- Fiction; Women immigrants -- Fiction; Married women -- Fiction; Puritans -- Fiction; Adultery -- Fiction; Revenge -- Fiction; Clergy -- Fiction; Puritans -- Massachusetts -- Fiction; Boston (Mass.) -- History -- Colonial period, ca. 1600-1775 -- Fiction; Massachusetts -- History -- Colonial period, ca.1600-1775 -- Fiction; Psychological fiction; Historical fiction